Pendampingan Penerapan SOP Pengambilan Sampel Air Minum di UPT Laboratorium Kesehatan Riau - Desi Susanti; M Kamali Zaman; Sangap Daniel T; Herniwanti Herniwanti (Jurnal Medika: Medika, 2026)
Drinking water sampling is a critical stage in water quality testing, as it determines the reliability of laboratory results and serves as a basis for public health decision-making. This residency activity aimed to analyze the implementation of Standard Operating Procedures (SOPs) for drinking water sampling at the Environmental and Health Laboratory Unit of the Riau Provincial Health Office. The study employed a qualitative case study approach through observations, in-depth interviews, and document review. Problem prioritization was conducted using the Urgency, Seriousness, and Growth (USG) method, while root cause analysis was performed using a fishbone diagram. The findings revealed that SOP implementation by sample submitters had not fully complied with established standards, particularly regarding the use of sterile containers, sampling techniques, labeling, and sample storage and transportation. These deficiencies may compromise sample integrity and result in laboratory data that do not accurately represent actual water quality conditions. Therefore, continuous education, improved SOP dissemination, and the development of simple and practical sampling guidelines are recommended to enhance compliance and ensure the reliability of drinking water quality testing results.